Targeting HOX/PBX dimer formation as a potential therapeutic option in esophageal squamous cell carcinoma - Shen, Lu‐Yan (Cancer Sci, 2019)
Homeobox genes are known to be classic examples of the intimate relationship between embryogenesis and tumorigenesis, which are a family of transcriptional factors involved in determining cell identity during early development, and also dysregulated in many malignancies. Previously, HOXB7, HOXC6 and HOXC8 were found abnormally upregulated in esophageal squamous cell carcinoma (ESCC) tissues compared with normal mucosa and seen as poor prognostic predictors for ESCC patients, and were shown to promote cell proliferation and anti‐apoptosis in ESCC cells. These three HOX members have a high level of functional redundancy, making it difficult to target a single HOX gene. The aim of the present study was to explore whether ESCC cells are sensitive to HXR9 disrupting the interaction between multiple HOX proteins and their cofactor PBX, which is required for HOX functions. ESCC cell lines (KYSE70, KYSE150, KYSE450) were treated with HXR9 or CXR9, and coimmunoprecipitation and immunofluorescent colocalization were carried out to observe HOX/PBX dimer formation. To further investigate whether HXR9 disrupts the HOX pro‐oncogenic function, CCK‐8 assay and colony formation assay were carried out. Apoptosis was assessed by flow cytometry, and tumor growth in vivo was investigated in a xenograft model. RNA‐seq was used to study the transcriptome of HXR9‐treated cells. Results showed that HXR9 blocked HOX/PBX interaction, leading to subsequent transcription alteration of their potential target genes, which are involved in JAK‐signal transducer and activator of transcription (STAT) activation and apoptosis inducement. Meanwhile, HXR9 showed an antitumor phenotype, such as inhibiting cell proliferation, inducing cell apoptosis and significantly retarding tumor growth. Therefore, it is suggested that targeting HOX/PBX may be a novel effective treatment for ESCC.